Enhancing Maharah Kalam Proficiency Through the Direct Method and Instructional Video Media - Effendi, Sulaiman (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This study investigates the effectiveness of Arabic language learning by utilizing the direct method of integrating video media and infocus technology at Manahijussadat and El-Karim Pesantren, Lebak-Banten. Employing a mixed-methods approach, the research combines quantitative and qualitative analyses to evaluate the impact of this teaching method on students' language skills, particularly in listening and speaking. Data collection methods included pre-tests, post-tests, classroom observations, and interviews with students and teachers. The results indicate a significant improvement in students' Arabic proficiency, as evidenced by increased test scores and enhanced confidence in speaking Arabic. Using videos as visual aids enriched the learning environment, making lessons more engaging and relatable, while in-focus technology facilitated interactive and dynamic instruction. The Direct Method emphasized immersion and active participation, allowing students to practice real-life conversational skills. Teachers reported that combined video and infocus tools increased student motivation and focus during lessons. However, technical difficulties and the need for teacher training in media utilization were identified. This research underscores the potential of integrating modern teaching aids with traditional methodologies to enhance Arabic language education, particularly in Islamic boarding schools. Recommendations for future improvements and broader applications are also discussed.